The disability-adjusted life years (DALYs), prevalence and incidence of scabies, 1990-2021: A systematic analysis from the Global Burden of Disease Study 2021. - Jiajia Li; Zehu Liu; Xiujiao Xia (PLoS Neglected Tropical Diseases)
Background Current literature lacks a recent global analysis of scabies. This study aims to analyze the burden and epidemiological characteristics of scabies using data from the Global Burden of Disease (GBD) 2021 study. Methodology/principal findings The analysis assessed disability-adjusted life years (DALYs), prevalence, and incidence of scabies from 1990 to 2021, stratified by geographic location, socio demographic index (SDI), gender, and age. In 2021, scabies caused 5.3 million DALYs, 206.6 million prevalence, and 622.5 million incidence, primarily affecting children and young people. The burden was heaviest in middle SDI regions and lowest in high SDI regions. Oceania, Tropical Latin America, and East Asia ranked as the top three regions in global scabies burden. Nationally, Fiji, Guam, Tonga, Tuvalu, and Northern Mariana Islands had the highest age-standardised DALY rates. From 1990 to 2021, global age-standardized rates (ASRs) of DALYs, prevalence, and incidence for scabies declined, while the absolute numbers increased. These ASRs showed an upward trend in high and high-middle SDI regions, with significant increases in Central Latin America and high-income North America. Larger burden increases were observed in Sri Lanka, the United States of America, and Mexico compared to other countries and territories. In terms of age, these ASRs increased from 40, particularly for women and the elderly. Conclusions/significance The global scabies burden was higher in tropical regions, particularly among children and young people, in 2021. Between 1990 and 2021, the burden increased in higher SDI regions, Central Latin America, and high-income North America, warranting focused attention. Additionally, the rising burden among adults over 40, particularly women and the elderly, highlighted the need for targeted interventions.